Analysis of LEO Satellite Network Performace according to Phasing Factor: Polar Region Boundary, Minimun Elevation angle - Chu, Heon Woo; Kim, Tae Yoon; Kim, Jae Hyun (International Conference on Ubiquitous and Future Networks, ICUFN, 2024)
The deployment model of low-Earth orbit (LEO) satellites astonishingly affects LEO satellite network performance. The deployment of satellites generates a polar region that reduces communication performance. Due to the relative velocity between satellites, inter satellite link is impossible in the polar region. The relative velocity between satellites is caused by the phase offset defined by the phasing factor. Therefore, since the polar region is affected by the phasing factor, it should be considered in the satellite network design. In this paper, we analyze the polar region boundary and minimum elevation angle of the LEO satellite network according to the phasing factor. The analysis of the polar region is demonstrated considering the Iridium and OneWeb LEO satellite constellations. Simulation results show that the polar region boundary differs by up to 19 degrees, and the minimum elevation angle of the ground station differs by up to 2.8 degrees depending on the phasing factor.
Keywords: Deployment models; Earth orbits; Elevation angle; Low earth orbit; Low earth orbit satellites; Phasing factor; Polar Regions; Region boundaries; Relative velocity; Satellite network; elevation angle; Low Earth orbit; phasing factor; polar region